Deciphering the Urinary Microbiota Repertoire by Culturomics Reveals Mostly Anaerobic Bacteria From the Gut - Dubourg, Grégory; Morand, Aurélie; Mekhalif, Fatima; Godefroy, Raphael; Corthier, Alice; Yacouba, Abdourahamane; Diakite, Ami; Cornu, Florent; Cresci, Marina; Brahimi, Samy; Caputo, Aurélia; Lechevallier, Eric; et al. (Frontiers in Microbiology, 2020)
Human urine was considered sterile for a long time. However, 416 species have been previously cultured, including only 40 anaerobic species. Here, we used culturomics, particularly those targeting anaerobes, to better understand the urinary microbiota. By testing 435 urine samples, we isolated 450 different bacterial species, including 256 never described in urine of which 18 were new species. Among the bacterial species identified, 161 were anaerobes (35%). This study increased the known urine repertoire by 39%. Among the 672 bacterial species isolated now at least once from urine microbiota, 431 (64.1%) were previously isolated from gut microbiota, while only 213 (31.7%) were previously isolated from vagina. These results suggest that many members of the microbiota in the urinary tract are in fact derived from the gut, and a paradigm shift is thus needed in our understanding.